Associations between vision impairment and driving and the effectiveness of vision-related interventions: protocol for a systematic review and meta-analysis - Nguyen, Helen (BMJ Open, 2020)
INTRODUCTION: Driving is one of the main modes of transport with safe driving requiring a combination of visual, cognitive and physical skills. With population ageing, the number of people living with vision impairment is set to increase in the decades ahead. Vision impairment may negatively impact an individual’s ability to safely drive. The association between vision impairment and motor vehicle crash involvement or driving participation has yet to be systematically investigated. Further, the evidence for the effectiveness of vision-related interventions aimed at decreasing crashes and driving errors has not been synthesised. METHODS AND ANALYSIS: A search will be conducted for relevant studies on Medline (Ovid), EMBASE and Global Health from their inception to March 2020 without date or geographical restrictions. Two investigators will independently screen abstracts and full texts using Covidence software with conflicts resolved by a third investigator. Data extraction will be conducted on all included studies, and their quality assessed to determine the risk of bias using the Joanna Briggs Institute Critical Appraisal Tools. Outcome measures include crash risk, driving cessation and surrogate measures of driving safety (eg, driving errors and performance). The results of this review will be reported using the Preferred Reporting Items for Systematic Review and Meta-Analysis guideline. Meta-analysis will be undertaken for outcomes with sufficient data and reported following the Meta-analyses of Observational Studies in Epidemiology guideline. Where statistical pooling is not feasible or appropriate, narrative summaries will be presented following the Synthesis Without Meta-analysis in systematic reviews guideline. ETHICS AND DISSEMINATION: This review will only report on published data thus no ethics approval is required. Results will be included in the Lancet Global Health Commission on Global Eye Health, published in a peer-reviewed journal and presented at relevant conferences. PROSPERO REGISTRATION NUMBER: CRD42020172153.